Genital Epstein Barr Virus is associated with higher prevalence and persistence of anal human papillomavirus in HIV-infected men on antiretroviral therapy. Issue 1 (December 2015) - Gianella, Sara; Ginocchio, Christine; Daar, Eric; Dube, Michael; Morris, Sheldon
Abstract Background Epstein Barr virus (EBV) and human papillomavirus (HPV) can co-exist in pharyngeal and cervical malignancies. However, the natural history and factors associated with persistent HPV infection among HIV-infected men who have sex with men (MSM) are unclear. Methods 131 HIV-infected MSM were followed for 48 weeks and screened for multiple co-infections, including seminal EBV DNA and high risk (HR)-HPV messenger RNA (mRNA) at several sites (semen, anal, pharynx). Primary analysis tested if seminal EBV shedding was associated with increased prevalence of HR-HPV at baseline using univariate tests and multivariable logistic regression. In participants with detectable anal HR-HPV at baseline, we tested if presence of seminal EBV shedding at baseline was also predictive of reduced HR-HPV clearance by log-rank test (over 48 weeks of follow-up). Results Baseline prevalence of HR-HPV was: anal 44 % (N  = 54/121); pharynx 3.8 % (N  = 5/131); semen 7.1 % (N  = 7/98). Seminal EBV shedding was present in 28 % of participants and was associated with more than double the prevalence of detectable anal HR-HPV mRNA (71.4 % for EBV shedders versus 33.3 % for non-shedders, p  < 0.01). In participants with detectable anal HR-HPV at baseline, we found increased persistence of HR-HPV over 48 weeks of follow-up (measured as time to first negative HR-HPV test in the EBV shedding group (p  < 0.01). Conclusions Seminal EBV shedding was associated with an increased risk of having detectable anal HR-HPV in a cohort of HIV-infected MSM on suppressive ART. Future studies should examine if co-infection with EBV and HR-HPV may act synergistically in pathogenesis of anal cancer in HIV-infected individuals.